Linguistic interference and its realization in different language layers - Yusupova Shahzoda Tohirjon qizi (Zien Journals, 2022)
Language as a social phenomenon is closely related to society, a group of people. Language is formed and developed in society. This cannot be denied at all. The fact that language is the main tool in human interaction and communication is an important factor that shows its integral connection with society. Linguistic interference as a social and linguistic phenomenon, is learned by sociolinguistics. The theoretical views on language interference and the occurrence of linguistic interference in different language layers are analysed in this article.
Keywords: language interference; native language; target language; bilingual